Find the general
Rearranging all the terms we get:
Integrating both the sides we get:
⇒log|1 - ex| = log|tany| - logc
⇒log|1 - ex| + logc = log|tany|
⇒tany = c(1 - ex)
Ans: tany = c(1 - ex)
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation